A Rugulopteryx okamurae-Based Biostimulant Enhances Growth and Phytochemicals in Lettuce - Tatiana P. L. Cunha-Chiamolera; Tarik Chileh-Chelh; Mohamed Ezzaitouni; Miguel Urrestarazu; Juan de Dios Carrillo Montalbán; José Luis Guil-Guerrero (Horticulturae)
This study investigates the potential of a biostimulant derived from the invasive brown alga Rugulopteryx okamurae (RoB) to enhance lettuce growth and improve its phytochemical profile. The extraction of the biostimulant was optimized through the implementation of a Box–Behnken design, and the resulting extract was then compared with a commercial Ascophyllum nodosum-based product (AnB). This comparison was made under both optimal and suboptimal fertigation conditions in a controlled, soilless culture. Lettuce plants were monitored for water and nutrient uptake, growth parameters, and accumulation of key phytochemicals such as carotenoids, tocols, sterols, and squalene. RoB significantly increased fresh and dry biomass, with enhanced nitrate and potassium uptake, in comparison to standard nutrient solution controls (p < 0.05). Treatments incorporating RoB consistently resulted in higher concentrations of lutein, β-sitosterol, and squalene, particularly under suboptimal conditions (p < 0.05), thus suggesting a strong biostimulant effect that mitigates nutrient stress. Furthermore, principal component analysis demonstrated that biostimulant application induces distinct metabolic profiles, highlighting the coordinated regulation of antioxidant pigments and sterol compounds. The findings support the dual benefits of algae-derived biostimulants in promoting sustainable crop production by improving yield quality and increasing health-promoting phytochemicals, paving the way for innovative, eco-friendly fertilization practices in modern agriculture.